2017
DOI: 10.3390/ijerph14030306
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Remobilisation on Riverbed Sediment Disturbance in Experimental Flumes and a Human-Impacted River: Implication for Water Resource Management and Public Health in Developing Sub-Saharan African Countries

Abstract: Resuspension of sediment-borne microorganisms (including pathogens) into the water column could increase the health risk for those using river water for different purposes. In the present work, we (1) investigated the effect of sediment disturbance on microbial resuspension from riverbed sediments in laboratory flow-chambers and in the Apies River, Gauteng, South Africa; and (2) estimated flow conditions for sediment-borne microorganism entrainment/resuspension in the river. For mechanical disturbance, the top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Because of possible water loss during the incubation, sample vials were regularly weighed to monitor the water content of the water–sediment system; and if necessary, water content was adjusted with HPLC‐grade water. After each addition, samples were gently shaken (without resuspension of sediment fines to avoid the disturbance of sediment‐borne microorganisms [Abia et al ]) to ensure aerobic conditions. Triplicate subsamples of sterilized and nonsterilized sediments were withdrawn at 0, 3, 7, 14, 28, 56, and 90 d following the start of the present study and immediately stored in a freezer at –22 °C until analysis (analysis occurred within 1 wk).…”
Section: Methodsmentioning
confidence: 99%
“…Because of possible water loss during the incubation, sample vials were regularly weighed to monitor the water content of the water–sediment system; and if necessary, water content was adjusted with HPLC‐grade water. After each addition, samples were gently shaken (without resuspension of sediment fines to avoid the disturbance of sediment‐borne microorganisms [Abia et al ]) to ensure aerobic conditions. Triplicate subsamples of sterilized and nonsterilized sediments were withdrawn at 0, 3, 7, 14, 28, 56, and 90 d following the start of the present study and immediately stored in a freezer at –22 °C until analysis (analysis occurred within 1 wk).…”
Section: Methodsmentioning
confidence: 99%
“…On top of the microbial food web changes, sediment contamination is another causal factor affecting the benthic biota, a significant food source for fish [11,12,13,14]. Additionally, resuspension of sediment micro-organisms into the water column can increase the health risk for those who use water [15]. It is often reported that high concentrations of heavy metals in sediment can lead to their accumulation in the internal organs of crustaceans and shellfish [16].…”
Section: Introductionmentioning
confidence: 99%
“…Among the 1121 bacterial genera detected in sediment samples, the 17 dominant bacterial genera (mean relative abundance > 0.5%) are shown in Figure 5b. The top 6 genera were shared in both sediment and water in each condition, including Exiguobacterium (mean: 15.4%), Citrobacter (mean: 7.4%), Acinetobacter (mean: 7.0%), Pseudomonas (mean: 3.7%), Methylotenera (mean: 1.8%), and Ramlibacter (mean: 1.5%), as the genera would exchange between the interactional and interdependent habitats (water and sediment) [54]. Similarly to the water, the abundances of genera Exiguobacterium , Citrobacter , Acinetobacter , and Pseudomonas showed a significant increase with the enhanced water disturbances ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The physicochemical properties of the sediment were basically stable along the timescale from week 0 to week 5 (see Table S1). Thus, the regular change of the bacteria in the sediment might be caused by hydrodynamic shear stress [54]. Moreover, no significant regularity was found for the abundance of other genera.…”
Section: Resultsmentioning
confidence: 99%